Gravity And Magnetic Data Analysis To Detect The Basement Rock Structure At Sungai Pahang Delta Area - Mohd Noh, Khairul Arifin (2008)
The objective of this study is to model and establish a geological structure, mainly the basement rock, using potential field analysis. Two potential field methods, i.e. gravitational field and magnetic field were used in this study. The coastal margin sedimentary basin at Sungai Pahang Delta in Pekan, Pahang was chosen as the study site. This is to identify the basement rock structure due to delta development such as fault zone evolution, basement expansion and compaction. The data were interpreted both qualitatively and quantitatively. The qualitative interpretation is based on anomalies on the contour maps, and the quantitative interpretation is based on data modeling. There is good correlation between the gravitational and the magnetic field methods since the same features are found at the same locations. The result from the magnetic field method shows that the basement rock contains extended basalt intrusion. However, the gravitational data show a more localized intrusion and the presence of a metamorphism contact zone.